Students' situational motivation in climate education – a multilevel profile approach - Ronkainen, Inka; Vesterinen, Veli-Matti; Lavonen, Jari; Järvinen, Jussi; Malmberg, Lars-Erik; Turkkila, Miikka; Salmela-Aro, Katariina (Elsevier BV, 2025)
In the present study, we aimed to identify how students' motivation varied in various learning situations in climate education. The motivation was evaluated through interest, competence, perceived task difficulty, effort and anxiety based on situated expectancy-value theory. Using ecological momentary assessment, we collected data from 3695 situations of 354 Finnish upper secondary school students. By applying Multilevel Latent Profile Analyses, six situational motivation patterns were identified: Amotivating situations (15 %), Difficult situations (9 %), Moderately motivating situations (50 %), Low demanding situations (12 %), Easy situations (9 %), and Highly motivating situations (5 %). Situational patterns were differently associated with various learning activities. Based on the relative prevalence of situational patterns, three student motivation profiles were identified: Weakly motivated (21 %), Moderately motivated (59 %), and Interested and competent (20 %). Results showed that there are more science programme students and males in the Interested and competent profile. In addition, students in science programmes had higher test scores. Educational relevance statement: Climate change is an important part of the Finnish school curriculum today. However, research has not yet found the single best way to motivate students to learn about it, including how to mitigate or adapt to it. This highlights the need to find new ways to motivate students on these important topics. Therefore, we investigated students' motivation in several learning situations to gain information on how students' motivation varies in different learning activities in the climate education module. Our findings showed that motivation to learn about climate change varies from situation to situation and from student to student. No learning style is suitable for everyone, but our research suggests that project-based learning could be a good way to teach about climate change. The issues should first be explored together, and then students can come up with solutions to the problems themselves. In addition, the results showed that a previous interest in science leads to higher motivation. Men were found to have higher levels of interest and competence.